Concrete pavement slab under blast loads - Luccioni, Bibiana Maria (2006)
The main objective of this paper is the analysis of the behaviour of concrete pavements subjected to blast loads produced by the detonation of high explosive charges above them. This subject is of particular interest in terrorist attacks in cities, since important conclusions about the location and magnitude of the explosive charge can be drawn from simple observation of the pavement damage. Experimental results for a concrete slab lying on the ground and subjected to blast loads are presented. The slab was lying on the ground and was tested with different amounts of explosive suspended in air over it. Numerical results are compared with those obtained with a simplified plastic limit analysis and those obtained with two types of numerical simulations performed with two different codes. Some conclusions about the effect of the blast load on the concrete slab and about different tools available for the analysis of this type of problem are stated in the paper.